Ansiedad infantil y rendimiento académico, en los estudiantes de tercer año de educación general básica de la Unidad Educativa "Once de Noviembre", en el año lectivo 2016-2017 - Carrillo Fonseca, Xiomara Alejandra (2017)
The study was carried out in the Educational Unit ¨Once de Noviembre¨ located in the province of Chimborazo in the present academic year 2016-2017,In thid research was carried out to the students of the Third Year of Gnereal Basic Education parallel (A, B, C, D). The purpose of this studywas to determine how Infantile Anxiety affects student achievement, a diagnosis anxiety level was necessary in the students and the performance could be identified to relate the children´s anxiety and the academic performance of the students. This important study was justified because in has a social value and demostrates the reason for the low performance in the classroom. T Besides, the theory of the John Gillis Infant Anxiety Questionnaire was supported. The research was undertaken from the perspective according to the type of descriptive and field study with a diagnostic design. The population there were 150 students from the Third Parallel Years (A, B, C, and D), being of a diagnostic type was considered the entire population, It is imporant to mention that the CAS test was used consisting of 20 direct and indirect questions. The applied processing of data allowed to determining that the common anxiety level in the students was normal with 56%. This information led to the following conclusions. The diagnosis of child Anxiety in the above mentioned students was normal and academic performance was not affect, In other words child anxiety and academic perfomance are related to a mastery of the required learning in academic performance.